2020
DOI: 10.33988/auvfd.590696
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sodium bentonite on growth performance and some blood parameters in post-weaning Tuj breed lambs

Abstract: The purpose of this study was to investigate the effect of sodium bentonite supplementation on fattening performance and some blood parameters in Tuj lambs. In the study, 18 male lambs were divided into 3 groups. While the control group was fed with basal ration, the experimental groups were fed with sodium bentonite supplementation 1% and 2% dose in addition to the basal ration. On the 0 th , 15 th , and 30 th days of the study, there was no statistically significant difference between groups in terms of mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Studies conducted on antioxidant properties of bentonite clays in livestock are very limited. Aydin et al (2020) described that SB supplementation to the Tuj breed of lambs increased MDA and antioxidant enzyme levels in blood plasma. On the contrary, several researchers reported that dietary clay minerals improved TAC values in layers (Qu et al 2018), and reduced MDA levels in sows (Papadopoulos et al 2016) and broilers (Safaei et al 2016;Morshdy et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies conducted on antioxidant properties of bentonite clays in livestock are very limited. Aydin et al (2020) described that SB supplementation to the Tuj breed of lambs increased MDA and antioxidant enzyme levels in blood plasma. On the contrary, several researchers reported that dietary clay minerals improved TAC values in layers (Qu et al 2018), and reduced MDA levels in sows (Papadopoulos et al 2016) and broilers (Safaei et al 2016;Morshdy et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Control fed with the basal diet and treatment groups fed with 0.5%, 1.0%, and 2.0% SB, respectively. Levels were determined according to the study conducted by Aydin et al (2020). SB was supplied from a local company in Türkiye (Muktibont-B, Sanita, İstanbul, Türkiye).…”
Section: Feeding Trialmentioning
confidence: 99%
See 2 more Smart Citations
“…Albumin fraction in the ureatreated rice straw rations was unaffected by the supplementation of bentonite at levels of 2.5 and 5% when compared to the control (Mohsen and Tawfik, 2005). Moreover, Aydin et al (2020) reported that the supplementation of sodium bentonite at rates of 1% and 2% to lambs' diets had no significant impact on the albumin, total protein, or globulin values of the lambs. Similarly, EI-Gendy (1985) reported that the calves fed urea-treated diets containing 0% or 4% bentonite did not experience any changes in blood protein content.…”
Section: Blood Metabolitesmentioning
confidence: 99%